J MATERN CHILD HEALTH 2017
DOI: 10.26911/thejmch.2017.02.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Education, Psychosocial Stress, Nutritional Status at Pregnancy, and Family Income, on Birthweight in Nganjuk, East Java

Abstract: Background: Low birth weight (LBW) is one of the primary causes of infant mortality. It shares 27% of infant mortality rate (IMR). The Indonesian Demographic and Health Survey in 2007 reported that the IMR was 34 deaths per 1,000 live births. As much as 30.3% of this rate was accounted by LBW. As such LBW is an important global public health issue. Countries around the world have committed to overcome this problem. This study aimed to investigate the effects of maternal education, psychosocial stress, nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
1
5
0
8
Order By: Relevance
“…This study result is in line with the study result by Nurahmawati et al, (2017), which found that there was a direct positive effect between the size of pregnant women's mother's upper arm circumference on the weight of the newborn. Another study, according to Ekayani (2014) also showed that maternal MUAC < 23.5 have 5 times the risk of giving birth to babies with LBW (OR= 5.54; 95% CI= 2.65 to 11.60).…”
Section: Positive Effect Of Maternal Muacsupporting
confidence: 92%
“…This study result is in line with the study result by Nurahmawati et al, (2017), which found that there was a direct positive effect between the size of pregnant women's mother's upper arm circumference on the weight of the newborn. Another study, according to Ekayani (2014) also showed that maternal MUAC < 23.5 have 5 times the risk of giving birth to babies with LBW (OR= 5.54; 95% CI= 2.65 to 11.60).…”
Section: Positive Effect Of Maternal Muacsupporting
confidence: 92%
“…Terdapat pengaruh positif LiLA Ibu secara langsung yang signifikan secara statistik antara terhadap berat badan lahir (Nurmayanti et al, 2017), dengan demikian LiLA Ibu ≥ 23.5 cm memberikan efek protektif terhadap kejadian bayi berat lahir rendah (Nurahmawati et al, 2017).…”
Section: Pengaruh Status Gizi (Lila Ibu)unclassified
“…Stres biposikososial ibu hamil dapat menurunkan berat lahir (Nurmayanti et al, 2017).Stres psikososial rendah dapat menurunkan kelahiran bayi berat lahir rendah (Nurahmawati et al,2017). Woods et al (2010), menemukan dari hasil penelitiannya mengenai stres psikososial antenatal menggunakan kuesioner Curry et al (1998), yaitu kuesioner Prenatal Psychosocial Profile: Stress Scale, sebagian besar wanita hamil sebanyak 78% mengalami stres rendah selama masa kehamilan.…”
Section: Pengaruh Status Gizi (Lila Ibu)unclassified
See 2 more Smart Citations